COMPUTATIONAL and TEORIC INVESTIGATION of the EFFECTS of FINNED TRICKLEVENT SYSTEM on BUILDING ENERGY SAVINGS - Sökmen, Kemal Furkan; Ergüner, Burhan; Akin, İlknur (Kütahya Dumlupinar University, 2022)
In our study, the effects of the finned Tricklevent passive air condition system on building energy savings were investigated. The system has been patented internationally with the patent number 2013/08326. A 14 m2 sample prototype office room was built for the study. Numerical studies were performed with FloEFD software. Theoretical calculations and numerical work values confirmed each other. In the analyses, independence from mesh was studied. The solar load is defined as 1009 W/m2. Office exterior windows are designed with a thickness of 6 mm and an air gap of 16 mm. In the study, it was determined that there was a fresh air inlet at a volumetric flow rate of 0.024 m3/s in the prototype office. It has been determined that the finned Tricklevent system cools the hot air coming from the outside environment and takes it in with a temperature drop of 5-6 o C. When the system is operated at the same time as the air conditioner, the air conditioner set temperature can be adjusted to higher temperatures, saving 28 kWh/m2 of energy and reducing the carbon footprint by 15.4 kg/m2. With the sequential operation of the system with the air conditioner, 21 kWh/m2 of energy was saved in a 3-hour period, while a carbon footprint of 11.5 kg/m2 was reduced.
3191144
Keywords: Engineering; Mühendislik